Antimicrobial activity of de novo designed cationic peptides against multi-resistant clinical isolates - Faccone, Diego Francisco (2013)
Antibiotic resistance is one of the main problems concerning public health or clinical practice. Antimicrobial peptides appear as good candidates for the development of new therapeutic drugs. In this study we de novo designed a group of cationic antimicrobial peptides, analyzed its physicochemical properties, including its structure by circular dichroism and studied its antimicrobial properties against a panel of clinical isolates expressing different mechanisms of resistance. Three cationic alpha helical peptides exhibited antimicrobial activity comparable to, or even better than the comparator omiganan (MBI-226).